PENERAPAN MODEL KOOPERATIF TIPE MAKE A MATCH DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA BERBANTUAN MEDIA POP UP BOOK PADA PEMBELAJARAN MATEMATIKA KELAS IV SDN 003/IX SENAUNG - Ayuni Shakila; Eka Sastrawati; Issaura Sherly Pamela (Universitas Bhinneka PGRI, 2024)
The research describes implementing the cooperative learning model of make a match type, aided by pop-up book media, to boost fourth-grade students' motivation in elementary school mathematics. Conducted as Classroom Action Research, data collection involved observation, interviews, and documentary studies at SD Negeri 003/IX Senaung. Results showed improvement across cycles: in the first cycle, meeting I, 58.3% was categorized as